The Use of the Beautiful Novel by Eka Kurniawan as a Teaching Material: An Analysis Based on Grounded Theory - Rahmayati, Nisa Dwi; Saharudin, Saharudin; Sirullhaq, Muhammad; Musaddat, Syaiful (Raudhah Publisher, 2025)
The Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) initiated by the Education Standards, Curriculum, and Assessment Agency (BSKAP) issued a policy called